2008
DOI: 10.1111/j.1365-2567.2008.02829.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of SOCS‐1 signalling in B and T lymphocytes by hepatitis C virus core protein

Abstract: SummaryHepatitis C virus (HCV) infection is characterized by a strong propensity toward chronicity, autoimmune phenomena and lymphomagenesis, supporting a role for lymphocyte dysregulation during persistent viral infection. We have shown that HCV core protein inhibits T-cell functions through interaction with a complement receptor, gC1qR. Here, we further report that B cells also express gC1qR that can be bound by HCV core protein. Importantly, using flow cytometry, we demonstrated differential regulation of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 43 publications
(60 reference statements)
2
59
0
Order By: Relevance
“…Another associated disease, known as non-Hodgkin lymphoma, results directly from aberrant B cell proliferation (70). As previously mentioned, SOCS1 is decreased in B cells taken from HCV-infected patients (39) or those incubated with HCV core protein in vitro (74). Decreased SOCS1 expression correlates with increased STAT1 activation and with increases in both B cell proliferation and IgM/IgG production.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 72%
See 2 more Smart Citations
“…Another associated disease, known as non-Hodgkin lymphoma, results directly from aberrant B cell proliferation (70). As previously mentioned, SOCS1 is decreased in B cells taken from HCV-infected patients (39) or those incubated with HCV core protein in vitro (74). Decreased SOCS1 expression correlates with increased STAT1 activation and with increases in both B cell proliferation and IgM/IgG production.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 72%
“…This is accompanied by decreases in STAT1 activation, markers of general T cell activation, and JAK/STAT-mediated IFN-␥ production, a response which greatly impedes the ability of CTLs to effectively clear viruses and promotes chronic HCV infection. In contrast, HCV core protein decreases the levels of SOCS1 in B cells (39,74). This decrease correlates with increased STAT1 activation and markers of general B cell activation, as well as increased B cell proliferation and antibody (IgM and IgG) production.…”
Section: Virally Exploited Functions Of Socs Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to PD-1 dysregulation, we previously demonstrated that HCV core protein differentially regulated T and B lymphocyte functions by modulation of SOCS-1 (28)(29)(30)(31). To determine whether SOCS-1 is also involved in the negative regulation of M/M F IL-12 production during HCV infection, primary M/M F s were purified from healthy subjects and HCV-infected patients and stimulated with LPS/R848 for 24-48 h, followed by detection of SOCS-1 gene expression by RT-PCR and Western blotting.…”
Section: Pd-1 Expression Is Inversely Associated With Il-12 Productiomentioning
confidence: 99%
“…One microgram of RNA was reverse transcribed using a GeneAmp RNA PCR kit (Applied Biosystems, Foster City, CA). SOCS-1 primers and RT-PCR conditions were described as reported previously (29). To control for genomic DNA contamination, equal amounts of cDNA from each sample were PCR amplified without reverse transcription.…”
Section: Rt-pcrmentioning
confidence: 99%